If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 10x + -20 Reorder the terms: 5 + 5x = 10x + -20 Reorder the terms: 5 + 5x = -20 + 10x Solving 5 + 5x = -20 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 5 + 5x + -10x = -20 + 10x + -10x Combine like terms: 5x + -10x = -5x 5 + -5x = -20 + 10x + -10x Combine like terms: 10x + -10x = 0 5 + -5x = -20 + 0 5 + -5x = -20 Add '-5' to each side of the equation. 5 + -5 + -5x = -20 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = -20 + -5 -5x = -20 + -5 Combine like terms: -20 + -5 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 9x-5y=18 | | 12r^2=27+27r | | 2x+5=115-10x | | 12+2x=2-4x | | -4(t-1)+9t=8t-8 | | 6c^2+9c/3c | | -5(t-1)+7t=6t-6 | | n-14=16 | | 51-3x=10x+22 | | -5+6(x-3)=15x+3-9x | | -9(t+2)=54 | | 0.5x-0.3(10-3x)=-0.6(x-5) | | 13=13 | | 1/6x-3=5 | | -7/8v=35 | | 3+y/2=3y/4-2 | | x^2+10x+98=0 | | 6+6x=42+x | | -14-9=12 | | 6(a-7)+20=2(a-7) | | 5(5x-3)+5=-9 | | -22u+-1x= | | 9x-3=6x+39 | | 4-4x=-2x-12 | | 18-3x=-9x | | 3(y+2)=30 | | -4x=-35+3x | | -10-3x=-4x+4 | | -0.2j=-0.2 | | 4+0.16n=3 | | 74=-3+2(-3+2) | | 320=10(x+15)-30 |